Analisis tingkat kognitif soal pada buku matematika kelas IV kurikulum merdeka - Karomah, Adinda Khoirul; Istiyati, Siti; Surya, Anesa (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2023)
This research aims to (1) Describe the suitability of competency test questions with learning outcomes in mathematics textbooks for class IV independent curriculum, and (2) Describe the cognitive level of competency test questions for mathematics textbooks for grade IV independent curriculum according to the revised Bloom taxonomy. This research is a qualitative descriptive study. The data source in this research is the 2022 revised Independent Curriculum Class IV mathematics book. Data collection was carried out using document study techniques. The data validity testing technique used is investigator triangulation and increasing persistence. Data analysis uses analytical techniques according to Miles and Huberman. The results of this research are as follows: (1) There are still many competency test questions that are not in accordance with the learning objectives, namely around 68.57%, and 31.43% of the questions that are appropriate. (2) The composition of the most competency test questions is 31.43% C1 level, 28.57% C2 level, 8.57% C3 level, 11.43% C4 level, 5.71% C5 level, 14 C6 level .29%. It is hoped that the implications of this research can be used as material for consideration and evaluation in choosing books, especially in mathematics learning.